In vitro accuracy and inter-observer reliability of CT angiography in detecting intracranial aneurysm enlargement. (6th March 2019) - Al Kasab, Sami; Nakagawa, Daichi; Zanaty, Mario; Bathla, Girish; Policeni, Bruno; Soni, Neetu; Allan, Lauren; Hudson, Joseph; Limaye, Kaustubh; Ortega-Gutierrez, Santiago; Samaniego, Edgar A; Hasan, David
Abstract : Background and purpose: To evaluate the accuracy and inter-observer variability when CT angiography is used to identify unruptured intracranial aneurysm growth. Methods: Two silicone phantom models were used in this study. Each phantom had eight aneurysms of variable size. The size and location of aneurysms in phantom 1 were representative of real patient aneurysms who presented to our institution. Phantom 2 contained aneurysms in the same locations, but with enlargement in various directions. Three blinded board-certified neuroradiologists were asked to identify the size of each aneurysm in three dimensions using CT angiography. The individual enlargement detection rates and inter-observer agreement rates of aneurysm enlargement among the three experts were calculated. Results: The detection rate of aneurysm enlargement in one dimension was 58.3% among the three observers. Accurate detection of enlargement in all dimensions was 12.5% among the three observers. Detection accuracy was not related to the size of enlargement. Significant inter-observer measurement variability was present. Conclusion: The use of CT angiography was associated with a poor ability to identify aneurysm enlargementaccurately. Further human studies are required to confirm our findings.